Possible New Focus of Diphyllobothriasis, Central Europe - Tomáš Scholz; Roman Kuchta; Jan Brabec (Emerging Infectious Diseases)
Diphyllobothriasis is a human parasitic infection that is widespread in the Northern Hemisphere. Popular sport fish such as pike and perch are the source of human infection. We document the autochthonous origin of diphyllobothriasis in a popular tourist destination in Central Europe, which likely marks recent colonization of the parasite.